The Effect of Workload and Compensation on Employee Performance at the Bandung Port Health Office - Nuning Yayuk Wulandari (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study was conducted to analyze the effect of Workload and Compensation on Employee Performance. The study was conducted on employees of the Bandung Port Health Office. The research method used was quantitative with multiple linear regression analysis through SPSS statistical software series 27 for Windows. The research sample amounted to 72 people obtained by a saturated sampling technique, or the entire population was taken as a research sample. Observation, interviews, and questionnaires were used to carry out data collection techniques. The results of the study showed that Workload and Compensation had a positive and significant effect on Employee Performance, both partially and simultaneously. The results of the analysis showed that Workload and Compensation simultaneously affected Employee Performance by 48.5%, while the remaining 51.5% was the influence of other factors not examined in this study.